Atlas of Bone Marrow Pathology (Atlas of Anatomic Pathology,, 2018)
This text illustrates bone marrow aspirate, imprint and biopsy specimens showing characteristic features of a wide variety of neoplastic and non-neoplastic conditions. While the focus is on Wright-stained smears and hematoxylin-eosin stained biopsies, other key histochemical and immunohistochemical stains are illustrated that are vital for proper diagnosis. After a brief review of the normal bone marrow, reactive changes in the marrow are illustrated, including the bone marrow response in constitutional disorders and to metabolic changes throughout the body. This is followed by specific infectious disorders in the marrow and other non-neoplastic disorders. The remainder of the Atlas illustrates the various neoplasms that involve the bone marrow, including leukemias, lymphomas and non-hematopoietic neoplasms. The hematologic neoplasms are classified using the 2016 World Health Organization (WHO) classification. This overview of bone marrow disorders illustrates a wide variety of diseases that practicing pathologists and hematologists will encounter in their routine practice.